How does anxiety influence fluid reasoning?. Issue 3 (3rd July 2017) - Williams, Alisa M.; Prince, Pauline
ABSTRACT: Does anxiety influence fluid reasoning, either negatively or positively? The purpose of this article was to review much of the relevant current literature to answer this question. An individual's ability to employ fluid reasoning to solve novel problems must include the context of the circumstances, the individual's unique set of cognitive resources, one's ability to utilize previously acquired knowledge from similar situations, and to create a solution in a quick and effective manner. Working memory and creativity are cognitive skill sets that influence the efficiency and effectiveness of novel problem solving, while anxiety can be a crippling factor for some. This article aims to discuss the role of each of these factors the implementation of novel problem solving with a special emphasis on the role of development during adolescence.